2015
DOI: 10.4085/1062-6050-50.7.07
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Postural-Stability Deficits After Cryotherapy to the Ankle Joint

Abstract: Dynamic postural stability was adversely affected immediately after cryotherapy to the ankle joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 52 publications
5
15
1
1
Order By: Relevance
“…Results showed that performing activities became safer after cryotherapy by postural balance improvement after cold water immersion. It comes in agreement with Fullam et al , (2015) (19) who tested 29 male college elite-level athletes using Star Excursion Balance Test on the anterior (ANT), posterolateral (PL), and posteromedial (PM) reach directions before and after a cryotherapy application for 15-minute on ankle joint. They found a decrease in reach-distance scores for all directions after cryotherapy comparing to pre-cryotherapy balance results.…”
Section: Discussionsupporting
confidence: 89%
“…Results showed that performing activities became safer after cryotherapy by postural balance improvement after cold water immersion. It comes in agreement with Fullam et al , (2015) (19) who tested 29 male college elite-level athletes using Star Excursion Balance Test on the anterior (ANT), posterolateral (PL), and posteromedial (PM) reach directions before and after a cryotherapy application for 15-minute on ankle joint. They found a decrease in reach-distance scores for all directions after cryotherapy comparing to pre-cryotherapy balance results.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this study come in agreement with those obtained by Fullam et al [14] and Ahmed et al [31], who observed that dynamic postural stability was decreased immediately after 15 minutes of ankle joint cryotherapy application. They also corroborate a study by oliveira et al [23], who reported that cryotherapy impaired knee joint position sense in normal knees.…”
Section: Cold Modalitysupporting
confidence: 93%
“…dynamic standing balance assessment is considered one of the most appropriate assessments which represent the demands of the lower extremity during functional tasks [12]. dynamic balance is influenced by strength, flexibility, and coordination [13,14]. Studies have found that tissue extensibility and flexibility increase after heat modalities [15] and decrease after cold modalities [16]; consequently, dynamic balance may be altered immediately after cold or heat modalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Douglas ve ark., bu sonucu doğrulamışlardır; dinamik denge ölçümlerinin fonksiyonel görevler sırasında alt ekstremitenin taleplerini daha iyi yansıtabileceğini ve bu nedenle de statik dengeden daha uygun bir değerlendirme olabileceğini ileri sürmüşlerdir. 12,13 Williams ve ark., sağlıklı genç kişilerde ayağa uygulanan buz sonrasında, dinamik bir denge testi olan yıldız denge testinde ve diğer alt ekstremite performans testlerinde bir etkilenme bulmamışlardır. 14 Saha testi olarak da kullanılan ve üst ekstremitenin dinamik dengesini ölçen üst ekstremite Y denge testi (ÜEYDT), bir sporcunun kontralateral üst ekstremitede ağırlık taşımasını korur iken, serbest el ile ulaşma yeteneğinin niceliksel analizine izin veren bir araçtır.…”
Section: Sağlıklı Bireylerde Omuz Eklemiunclassified